2015
DOI: 10.1093/nar/gkv1514
|View full text |Cite
|
Sign up to set email alerts
|

Sliding of a 43S ribosomal complex from the recognized AUG codon triggered by a delay in eIF2-bound GTP hydrolysis

Abstract: During eukaryotic translation initiation, 43S ribosomal complex scans mRNA leader unless an AUG codon in an appropriate context is found. Establishing the stable codon–anticodon base-pairing traps the ribosome on the initiator codon and triggers structural rearrangements, which lead to Pi release from the eIF2-bound GTP. It is generally accepted that AUG recognition by the scanning 43S complex sets the final point in the process of start codon selection, while latter stages do not contribute to this process. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 74 publications
(119 reference statements)
1
30
0
Order By: Relevance
“…By contrast, eIF5 gave a relative advantage to the leaderless mRNA (Fig. 3b), probably by stimulating the 5′-terminal AUG recognition and blocking ribosomal sliding4344. Interestingly, eIF5B, the eukaryotic homolog of bacterial IF2, also differentially affected the reporter mRNAs translation (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…By contrast, eIF5 gave a relative advantage to the leaderless mRNA (Fig. 3b), probably by stimulating the 5′-terminal AUG recognition and blocking ribosomal sliding4344. Interestingly, eIF5B, the eukaryotic homolog of bacterial IF2, also differentially affected the reporter mRNAs translation (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…3b). This could be explained either by stabilization of the 48 S complex and inhibition of its sliding4445 or by stimulation of an alternative translation initiation pathway in a manner similar to bacterial, archaeal, and mitochondrial IF246; see below.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…108,109 On the other hand, long uORFs and short distances between uORF and main ORF impede reinitiation and thus correlate with increased repressiveness of the uORF. 91,110,111 Regulating the regulator -how uORF translation can be controlled Apart from such a constitutive mode of action, there is increasing evidence that uORF-mediated regulation itself can be dynamically regulated. In its simplest form of regulation, uORFs can either be selectively included or excluded during the production of the mRNA.…”
Section: Uorfs As Widespread Repressive Genetic Elementsmentioning
confidence: 99%
“…Moreover, changing the activity and concentration of eIF2 affects the general ability of ribosomes to reinitiate translation after uORFs. 91,110,111 Similarly, a study carried out in Arabidopsis thaliana has identified the target-of-rapamycin (TOR) pathway in conjunction with the S6 kinase (S6K) and the plant reinitiation factor eIF3h as more general regulators of reinitiation. 130 Induction of the TOR pathway by the plant hormone auxin leads to S6K-mediated phosphorylation of eIF3h, which promotes the assembly of reinitiating ribosomes.…”
Section: Uorfs As Widespread Repressive Genetic Elementsmentioning
confidence: 99%